MEDICAL BIOLOGY READ THE SCIENCE THE USE OF EDUCATIONAL FILMS - Firuza Ilxomovna Nazarova (Bright Mind Publishing, 2025)
Today higher education social requirements increase more than before, in this case biology teaching central to the policy of socio-economic, scientific and technological development must meet the requirements. Practical design is aimed at the direction of great importance for the teaching of biology at the time, the biological events students of agriculture, biotechnology, environmental protection and connection with other areas of life, it is important to get support. Educational in the subject of biology knowledge, skills, and skills to ensure the use of different means of education is important. Also in the exhibition is not important. Writing this article goal today science-biology lesson in the era of information technology and advanced technical students in using effective methods of give from the coverage of the film. The film is not simply to make a show of tutorials, but the process study, research, thought, and intended to apply in practice to the process which created the ground for me to become. Keywords: video, visual tools, educational materials, physiological processes, mastering, comparison, activation, scientific materials, repeat, synthesis, didactic cards, the one note.
Keywords: video, visual tools, educational materials, physiological processes, mastering, comparison, activation, scientific materials, repeat, synthesis, didactic cards, the one note.